Implementasi artificial intelligence marketing pada E-commerce : personalisasi konten rekomendasi serta dampaknya terhadap purchase intention - Setyawan, Abdur Rochman Tri (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The digital transformation that has now penetrated into business activities has encouraged the emergence of online buying and selling platforms, or what we often know as e-commerce. E-commerce was made because people wanted to buy and sell things online in a way that was easy for both buyers and sellers. This study aims to determine the impact of artificial intelligence on purchase intention in e-commerce. The variables tested are the influence of perceived usefulness, perceived ease of use, and attitude toward personalization on purchase intention on Shopee e-commerce. The sampling method in this study is probability sampling with a total of 150 respondents who are people of the Special Region of Yogyakarta with an age range of 18-40 years and are actively using Shopee e-commerce. Primary data was collected using a questionnaire method that has been tested for validity and reliability. Based on the results of data testing using the classical assumption test, descriptive analysis and multiple regression analysis, the results show that: (1) perceived usefulness has a positive and significant effect on attitude toward personalization, (2), perceived ease of use has a positive and significant effect on attitude toward personalization, and (3) attitude toward personalization has a positive and significant effect on purchase intention.